Collaboratively composing an argumentative essay: wiki versus face-to-face interactions - Ansarimoghaddam, Shokoufeh; Tan, Bee Hoon; Yong, Mei Fung (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study employed a qualitative case study method to compare learner-learner interaction on wiki and face-to-face collaborative writing in completing an argumentative essay. Face-to-face collaborative writing refers to in-class meeting of students to write essays collaboratively. Thirty ESL tertiary students from an intact class participated in the study. They were randomly divided into Group 1 and Group 2. Each of the two groups was further sub-divided into five smaller groups comprising three members. Group 1 discussed and wrote the essay on the wiki platform while Group 2 did the same task face-to-face in the classroom. One sub-group from both modes of writing was selected for in-depth comparison. Data were collected from the collaborative writing processes on the wiki platform and audio-recordings of face-to-face interactions, and also from semi-structured interviews. The findings revealed that the participants of both modes of writing were able to evaluate different viewpoints, and understand shortcomings and strengths through interaction in either of the collaborative learning contexts. The collaboration through both modes of writing showed that the participants not only displayed similar understanding, but also learned from each other through developing and sharing different perspectives on the same issues. Of the differences found between the two modes of collaborative writing, Wiki is a more effective platform for drafting and revising, while planning is easier done through face-to-face interaction. The study implies that either mode of collaborative writing can be adopted by ESL language instructors who aspire to practice the social-constructivist approach to writing instruction especially in a blended learning environment.